MEMBANGUN PEMAHAMAN KONSEP PERKALIAN SEBAGAI PENJUMLAHAN BERULANG PADA PESERTA DIDIK TUNARUNGU MELALUI MEDIA PAPAN PERKALIAN - Sofia Safienta Nur Rahma, Khadijah; Anjariyah, Deka; Nurul Imanah, Ulil (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Understanding the concept of multiplication is an essential foundation for students learning more complex arithmetic operations, including for deaf students whose learning characteristics differ due to hearing limitations. This study aims to describe the conceptual understanding of multiplication among deaf students after learning with a multiplication board medium combined with a direct instruction model. The study used a qualitative case study approach involving three seventh-grade deaf students at SLB B Pertiwi, Mojokerto City, selected through a total sampling technique. Data were collected through essay-type concept understanding tests, semi-structured interviews assisted by a sign language interpreter, and observation of learning activities, then analyzed following data reduction, data display, and conclusion drawing, with data validity tested through time triangulation. The results show that all three subjects, coded SF, SM, and SY, were able to meet the three concept understanding indicators studied: restating the concept of multiplication as repeated addition, distinguishing examples from non-examples of the concept, and selecting and applying the appropriate solving procedure to word problems. Nevertheless, individual variations were found: SF excelled in response speed but was limited in verbally expressing reasons, SM had strong memory and provided the most detailed written reasoning, while SY showed the most notable improvement in fluency from the first to the second stage. These findings indicate that concrete-visual media combined with structured learning can help deaf students understand the concept of multiplication meaningfully, while also affirming the importance of an approach that accommodates differences in verbal information processing speed among individual students.